1997
DOI: 10.1080/03079459708419238
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and immunohistochemistry of renal lesions due to avian infectious bronchitis virus in chicks uninoculated and previously inoculated with highly virulent infectious bursal disease virus

Abstract: SUMMARYA nephropathogenic strain of infectious bronchitis virus (IBV) was inoculated intra-tracheally into 14-day-old specific-pathogen-free chicks or ones previously inoculated with highly virulent infectious bursal disease virus (IBDV) at 7 days of age. The renal lesions were examined histopathologically and immunohistochemically at intervals up to 30 days post-inoculation. The mortality was 20% in the IBDV + IBV-inoculated group, but not in the IBV-inoculated one. Swollen and pale kidneys due to IBV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…These findings indicate IRFIBV32 isolate has a broad tissue distribution that includes respiratory, digestive, congenital, and urinary tract tissues; predominantly in urinary and digestive tracts. This result is in agreement with the previous studies about IBV distribution [6,22,24,25]. Chen and Itakura [24] reported that the tracheal lesions recovered faster in IBV inoculated groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings indicate IRFIBV32 isolate has a broad tissue distribution that includes respiratory, digestive, congenital, and urinary tract tissues; predominantly in urinary and digestive tracts. This result is in agreement with the previous studies about IBV distribution [6,22,24,25]. Chen and Itakura [24] reported that the tracheal lesions recovered faster in IBV inoculated groups.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with the previous studies about IBV distribution [6,22,24,25]. Chen and Itakura [24] reported that the tracheal lesions recovered faster in IBV inoculated groups. The nephropathogenic property of their IBV was longer lasting than the respiratory involvement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The kidney lesions of IB are principally those of an interstitial nephritis (Figure 4.7G and H) (35,36,155). The virus causes granular degeneration, vacuolation and desquamation of the tubular epithelium, and massive infiltration of heterophils in the interstitium in acute stages of the disease.…”
Section: Microscopicmentioning
confidence: 99%
“…From the respiratory tract, the virus spreads through the host via viremia (Jones and Jordan, 1972) to the epithelial cells of the renal tubuli (Chen and Itakura, 1996;Condron and Marshall, 1986;Purcell et al, 1976) and the ciliated epithelium of the oviduct (Crinion et al, 1971;Jones and Jordan, 1971). Here the virus causes respectively renal failure with urate obstruction due to tubular necrosis with mononuclear inflammation (Chen and Itakura, 1997;Jones, 1974), and oviductal necrosis and malformation leading to abnormal egg production and inability to lay (Chousalkar and Roberts, 2007). The severity of the disease in various organs depends on the IBV subtype and ultimately determines the mortality in chickens.…”
Section: Infectious Bronchitismentioning
confidence: 99%